2017
DOI: 10.3390/met7100399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weld Bead Shape on the Fatigue Behavior of GMAW Lap Fillet Joint in GA 590 MPa Steel Sheets

Abstract: Abstract:In this study, the effect of weld bead shape on the fatigue strength of lap fillet joints using the gas metal arc welding (GMAW) process was investigated. The base material used in the experiment was 590 MPa grade galvanealed steel sheet with 2.3 mm and 2.6 mm thickness. In order to make the four types of weld beads with different shapes by factors such as length, angle, and area, the welding process, wire feeding speed, and joint shape were changed. The stress-number of cycles to failure (S-N) curve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The fatigue test was carried out using a specimen with similar weld beads to minimize the effect of weld bead shape on the fatigue test. It was reported that the fatigue behavior varies depending on the bead shape of the weld [11]. The weld bead size was measured using the length parameter shown in Figure 10 according to the types of weld defects.…”
Section: Fatigue Behaviormentioning
confidence: 99%
See 3 more Smart Citations
“…The fatigue test was carried out using a specimen with similar weld beads to minimize the effect of weld bead shape on the fatigue test. It was reported that the fatigue behavior varies depending on the bead shape of the weld [11]. The weld bead size was measured using the length parameter shown in Figure 10 according to the types of weld defects.…”
Section: Fatigue Behaviormentioning
confidence: 99%
“…Fatigue fracture propagates from the root to the top of the plate when fatigue cracking occurs at the root and when fatigue cracking occurs at the weld toe, the fatigue fracture propagates down to the weld toe of the bottom plate. Hwang et al [11] reported that fatigue fracture propagated from the root to the top of the plate when fatigue cracks occurred at the root and fatigue crack propagated down to the weld toe of the bottom plate when fatigue cracks occurred at the weld toe. The applied load used for the measurement of static and fatigue strength can induce a very complicated distribution of normal and shear stresses in the lap joint [20][21][22].…”
Section: Fatigue Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the weld lines in the chassis parts affect the overall performances of the chassis parts. Additionally, the geometry of the weld bead has a dominant influence on the mechanical performance of the chassis parts, that is, on their tensile strengths and fatigue characteristics [5][6][7][8][9]. The bead geometry is composed of five parts, including the weld face, root, toe, leg, and throat.…”
Section: Introductionmentioning
confidence: 99%